What are the Causes and Consequences of Delayed Surgery for Pediatric Tibial Spine Fractures?. Issue 5 (31st May 2022) - Patel, Neeraj M.; Leska, Tomasina M.; Ganley, Theodore J.; Aoyama, Julien T.; Cruz, Aristides I.; Ellis, Henry B.; Fabricant, Peter D.; Green, Daniel W.; Jagodzinski, Jason E.; Johnson, Benjamin; Kushare, Indranil; Lee, Rushyuan J.; et al.
Background: The uncommon nature of tibial spine fractures may result in delayed presentation, diagnosis, and treatment. Elucidation of the contributing factors to such delays may provide an opportunity to improve patient care. Additionally, the outcomes of delayed surgery are unknown. Hypothesis/Purpose: The purpose of this study is to evaluate risk factors for, and consequences of, delayed surgical treatment of pediatric tibial spine fractures. Methods: We performed a retrospective cohort study of tibial spine fractures treated surgically at 10 institutions between 2000 and 2019. Demographic and pre-operative data were collected, as was intra-operative information and post-operative complications. Attention was focused on delays in evaluation and treatment, which were treated as both continuous and categorical variables. Surgery ≥21 days after injury was considered "delayed". Univariate analysis was followed by purposeful entry multivariate regression to adjust for confounding factors. Results: A total of 368 subjects (mean age 11.7±2.9 years) were included, 21.2% of which underwent surgery ≥21 days after injury. Patients who experienced delayed surgery had 3.8 times higher odds of being diagnosed with a TSF 1 or more weeks after injury [95% confidence interval (CI) 1.1-14.3, p=0.04], 2.3 times higher odds of having seen multiple clinicians prior to the treating surgeon (95% CI 1.1-4.8, p=0.02), 5.8 times higher odds of having magnetic resonance imaging 1 or more weeks after injury (MRI; 95% CI 1.6-20.8, p<0.007), and were 2.4 times more likely to have public insurance (95% CI 1.3-4.2, p=0.003). Meniscal injuries were encountered intra-operatively in 42.3% of those that had delayed surgery compared to 16.6% of patients that did not (p<0.001), resulting in 2.8 times higher odds in multivariate analysis (95% CI 1.6-5.0, p<0.001). Delayed surgery was also a risk factor for procedure duration longer than 2.5 hours (odds ratio 3.3, 95% CI 1.4-7.9; p=0.006). Patients who experienced delayed surgical management and an operation longer than 2.5 hours had 3.7 times higher odds of developing arthrofibrosis (95% CI 1.1-12.5, p=0.03). Conclusion: When surgery for a TSF was performed ≥21 days after injury, patients were at increased risk for concomitant meniscal pathology, longer case duration, and possibly post-operative arthrofibrosis. Those who experienced delays in diagnosis or MRI, saw multiple clinicians, and had public insurance were more likely to have a delay to surgery. These results provide an opportunity to optimize care for children that are at highest risk for delayed treatment.